Mineralogy and genesis of manganese pisolites from the Do Azul mine (Carajás, Brazil) - Cantorín Vílchez, Maritza Mercedes (2016)
In the Do Azul mine, the manganese pisoliths are scattered in irregular layers of lateritic rocks, which form small hills, covering the slopes and surfaces with colluvial materials from the Igarapé Do Azul plateau. They are packages that reach up to 8 meters thick and are of great importance for understanding the processes of formation of manganese superegenous deposits. The pisoliths have spherical, sub-spherical and also angular shapes, the size of their diameters varies from 0.5 to 8 mm and are normally made up of a nucleus, surrounded by concentric layers. For the most part, the cores and layers are well differentiated. The nuclei can occupy from 10 to 80% of the total volume of each pisolite and are mainly made up of Mn oxides and hydroxides such as: cryptomelan, pyrolusite, lithophorite, hollandite, todorokite and birnessite, also occurring gibbsite, kaolinite and anatase in variable amounts , and in some nuclei quartz is present. Fe and Al oxides and hydroxides predominate in the concentric layers, such as kaolinite, goethite, gibbsite and anatase, with cryptomelan and lithophorite lenses, also micro cavities filled with pyrolusite. These data demonstrate that the nuclei of the pisoliths represent the physical disaggregation of the underlying and adjacent materials, mainly manganese mineralization, and their layers, the aggregation of the superimposed lateritic profile by means of downhill transport. Pisoliths are excellent indicators for prospecting manganese mineralizations.